Quasi-stationary modelling of solidification in a latent heat storage comprising a plain tube heat exchanger. (December 2018) - Stamatiou, A.; Maranda, S.; Eckl, F.; Schuetz, P.; Fischer, L.; Worlitschek, J.
Highlights: Two-dimensional model of a latent heat storage with plain tube heat exchanger. Description of time-dependent solidification process of a phase-change material (PCM). Temperature-based approach with quasi-stationary approximation. Model validated experimentally with RT10. Low computational times (<1 min) and high accuracy. Abstract: In this paper, a two-dimensional model of a latent heat storage is presented. The model describes the time-dependent solidification of a phase-change material (PCM) around a plain tube heat exchanger. Heat transfer and energy balance equations are combined to predict the heat flow rate from the solidifying PCM to the heat transfer fluid. The model utilizes the temperature-based approach combined with a quasi-stationary approximation. In contrast to most solidification modelling approaches, the model is characterized by low computational complexity which enables the simulation of the entire storage volume instead of only a small section. The model is compared with experimental data obtained from a latent heat storage test-rig with a vertical plain tube heat exchanger. The predicted power output matched the experimental results very well, demonstrating the high accuracy of the simulations. This is the first report of a quasi-stationary model of a latent heat storage being validated with a PCM other than water and thus demonstrates the applicability of this approach in a wider range of PCM. The presented model can be used as a fast and accurate tool to design latent heat storage units as well as to analyse the performance of existing storage tanks.